A review of project of the controllers for an UPS - Guillardi Junior, Hildo; Amaral Serni, Paulo Jose [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
This paper presents a classical design methodology, review and comparison between different controllers applied to control the output stage of a UPS single-phase 127V @ 60Hz of 1kVA in islanded operation. The behavior is analyzed in regime through RMS value and voltage harmonic distortion, and transient according to IEC62040-3. Both cases for loads of different nature and power equal to the nominal UPS. For development of the prototype was used the IGBTs SKM75GB128D triggered by driver SKHI23-12R and the control has be implemented in a fixed-point DSP TMS320F2812.
Keywords: Classic control; DC-AC power converters; uninterruptible power systems (UPSs)